Virtual Looking. Home Movies as Historical Evidence in The Future Is Behind You (Abigail Child, 2004) - Anderson, Zachariah (Iluminace, 2022)
Twenty-first century scholars debate the epistemological and historiographic questions that emerge when once-private home movies are appropriated to support public-facing histories. Building on the work of Jaimie Baron, Catherine Russell, Jeffrey Skoller, and others, I approach archival filmmaking practices - in which filmmakers appropriate extant images for (re)use in alternative audiovisual contexts - as sites that make these questions and concerns analyzable. I turn to the archival film The Future Is Behind You (Abigail Child, 2004) as a space for exploring reflexive modes of looking at and appropriating home movies as historical evidence. Building on Skoller's analysis of the relationship between experimental filmmaking practices, history, and Gilles Deleuze's notion of "virtuality," I analyze director Abigail Child's historiographic methods as a process I call virtual looking at home movies. Virtual looking is an engaged, critical process through which an historian, filmmaker, and/or spectator disrupts home movies' surface-level content while exploring historical memories and experiences via imagined private perspectives. In The Future Is Behind You, Child manipulates and recontextualizes 16mm home movies in relation to one family member's imagined perspective and memories, which are described via superimposed digital text. I interpret Child's archival filmmaking processes of disruption and imagination as an invitation for further exploring reflexive strategies when appropriating and engaging with home movies in a variety of public historiographic settings.
Keywords: archive; history; archival filmmaking; home movies; historical evidence